2018
DOI: 10.1007/s00455-018-9882-y
|View full text |Cite
|
Sign up to set email alerts
|

Race Differences in Gastrostomy Tube Placement After Stroke in Majority-White, Minority-Serving, and Racially Integrated US Hospitals

Abstract: We sought to determine individual and system contributions to race disparities in percutaneous endoscopic gastrostomy (PEG) tube placement after stroke. Ischemic stroke admissions were identified from the Nationwide Inpatient Sample between 2007 and 2011. Hospitals were categorized based on the percentage of ethnic/racial minority stroke patients (< 25% ethnic/racial minorities ["majority-white hospitals"], 25-50% ethnic/racial minorities ["racially integrated hospitals"], or > 50% ethnic/racial minorities ["m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…While many studies of inequality in access to quality health care concentrate on the lower availability of health care, there is a growing body of literature reporting on the association between hospital quality and minority‐service hospital status across multiple health states and conditions. 4 , 5 , 8 , 10 , 13 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 Minority‐serving hospitals have also been shown to have lower scores for reported patient experience, despite findings that minority patients report better experiences overall. 12 , 50 , 51 A consistent finding has been that disparities in patient‐level health risks alone do not explain variation in quality between hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many studies of inequality in access to quality health care concentrate on the lower availability of health care, there is a growing body of literature reporting on the association between hospital quality and minority‐service hospital status across multiple health states and conditions. 4 , 5 , 8 , 10 , 13 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 Minority‐serving hospitals have also been shown to have lower scores for reported patient experience, despite findings that minority patients report better experiences overall. 12 , 50 , 51 A consistent finding has been that disparities in patient‐level health risks alone do not explain variation in quality between hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the idea that areas with higher percentages of racial and ethnic diversity tended to have lower‐performing hospitals, regardless of what specific racial or ethnic minority group predominated. While many studies of inequality in access to quality health care concentrate on the lower availability of health care, there is a growing body of literature reporting on the association between hospital quality and minority‐service hospital status across multiple health states and conditions 4,5,8,10,13,26–49 . Minority‐serving hospitals have also been shown to have lower scores for reported patient experience, despite findings that minority patients report better experiences overall 12,50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an elevated prevalence of poor nutrition in Black patients versus Caucasians [17]. Black patients had poorer nutritional intake (including fruits and vegetables), and older Black patients were at greater risk for malnutrition than their Caucasian counterparts [14,15,17]. Healthy food items are generally more expensive than less healthy choices, thereby limiting their availability to low-income populations [18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adequately managing malnutrition via interventions such as feeding tube placement is critical in improving outcomes. However, rates of PEG placement, and its risks, have been shown to differ among patients of different races and household incomes who have suffered a cerebrovascular accident, a major indication for the procedure [13,14]. Our goal is to determine if similar race-based differences exist in the identification of malnutrition in patients who have undergone PEG placement.…”
Section: Introductionmentioning
confidence: 99%